Applications of artificial intelligence in cancer immunotherapy: a frontier review on enhancing treatment efficacy and safety - Liu, Ji’an; Fu, Rao; Su, Yang; Li, Zhengrui; Huang, Xufeng; Wang, Qi; Shi, Zhengqin; Wei, Shouxin (Frontiers in Immunology, 2025)
Cancer immunotherapy represents a major breakthrough in oncology, particularly with immune checkpoint inhibitors (ICIs) and CAR-T cell therapies. Despite improved outcomes, challenges such as immune-related adverse events (irAEs) and treatment resistance limit clinical use. Artificial intelligence (AI) offers new opportunities to address these barriers, including target identification, efficacy prediction, toxicity monitoring, and personalized treatment design. This review highlights recent advances in AI applications for biomarker discovery, safety evaluation, gene editing, nanotechnology, and microbiome modulation, integrating evidence from clinical and preclinical studies. We also discuss future directions and challenges in applying AI to cancer immunotherapy, aiming to support further research and clinical translation.